Assessment of Physicochemical and Bacteriological Parameters of Bottled Drinking Water Marketed in Gilgit City and its Vicinity: Quality assessment of bottled drinking water of Gilgit - Hussain, Nazia; Nafees, Maisoor Ahmed; Sharista; Saif-Ud-Din (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
This study analyzed physicochemical and bacteriological parameters of packaged water sold in Gilgit city and its vicinity. Samples from source, market, and after the process were collected randomly from three different companies and analyzed from April 2017 to May 2017. Bacteriological parameters include Escherichia coli and Enterococci; it was further examined with conformity tests. The investigated physical parameters included (pH, Turbidity, Conductivity, Total Dissolved Solids). Some important chemical parameters like Total phosphorous and Total Nitrogen were assessed through a spectrophotometer. The results revealed that the Physicochemical parameters fell within WHO tolerable limits, pH ranged from 7.0 to 8.4, TDS were observed from 260 ppm to 40 ppm, Electrical conductivity was found between 91 μs-510 μs, Turbidity varied from 0.03 NTU to 0.52 NTU. The Total Nitrogen and Total Phosphorus range from 0.09 mg/L to 2.09 mg/L and 95 mg/L to 540 mg/L. The bacteriological parameters were unsatisfactory as some of the samples were contaminated with the E. coli and Enterococci. The maximum value for E. coli was 288 CFU/100 ml, and that of the Enterococci was 267 CFU/100 ml, which strongly violates the WHO specifications for bottled drinking water quality. Based on our findings, the Bacteriological examination of some samples is classified under the high-risk category since they are found to be unsafe for drinking. It is recommended there should be strict monitoring and surveillance of bottled water quality; sources should be protected, and awareness should be given to the public regarding its quality.